Effects of aggressive traits on cyberbullying: Mediated moderation or moderated mediation?. (August 2019) - Song, Minghua; Zhu, Zhuan; Liu, Shen; Fan, Hang; Zhu, Tingting; Zhang, Lin
Abstract: To explore the process of cyberbullying, the current study investigated the relationships among aggressive traits, beliefs about aggression, network public opinion, and cyberbullying. A questionnaire survey was conducted among 693 Chinese college students. Based on the findings, we constructed two competing models (mediated moderation and moderated mediation). The results revealed the following: (1) Aggressive traits and beliefs about aggression were all positively correlated with cyberbullying, aggressive traits were positively correlated with beliefs about aggression, and aggressive traits were negatively correlated with network public opinion. (2) The effect of aggressive traits on beliefs about aggression and cyberbullying was moderated by network public opinion. When network public opinion included irrational comments, aggressive traits directly and indirectly affected cyberbullying. When network public opinion included rational comments, aggressive traits only directly affected cyberbullying. Finally, (3) the effect of aggressive traits on cyberbullying was moderated by network public opinion and the moderating effect of network public opinion was partly realized through the mediating effect of beliefs about aggression. The findings contribute to our understanding of when and how aggressive traits affect cyberbullying. We found support for the mediated moderation model, and the results have implications for prevention and intervention in cyberbullying. Highlights: Aggressive traits significantly predicted beliefs about aggression and cyberbullying. Network public opinion moderated the aggressive traits and cyberbullying relation. Beliefs about aggression partly mediated the moderation effect of network public opinion. Parents and schools should correctly guide students' online behaviors.